GROWTH DRIVERS AND EMERGING TRENDS IN THE INDIAN AUTOMOBILE INDUSTRY - Singh, Dharmendra; Bhushan, Madhu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The automobile industry plays a crucial role in India’s GDP and employment generation. Despite challenges such as rising crude oil prices, semiconductor shortages, and supply chain disruptions, India remains the fourth-largest automobile market globally and is projected to secure the third position by 2026, indicating strong growth potential. The government’s proactive policies and regulatory support have further strengthened the sector. India has become a vital part of the global strategy for international vehicle manufacturers and component suppliers. While the industry is expanding rapidly, it must remain adaptable to evolving global market conditions and challenges. This study explores the latest trends shaping the global automobile industry and examines the obstacles faced by India’s automotive sector. Additionally, it highlights the key growth drivers and potential opportunities for major industry players in the coming years.